Digital Holographic Capture and Optoelectronic Reconstruction for 3D Displays - Damien P. Kelly; David S. Monaghan; Nitesh Pandey; Tomasz Kozacki; Aneta Michałkiewicz; Grzegorz Finke; Bryan M. Hennelly; Malgorzata Kujawinska (International Journal of Digital Multimedia Broadcasting)
The application of digital holography as a viable solution to 3D capture and display technology is examined. A review of the current state of the field is presented in which some of the major challenges involved in a digital holographic solution are highlighted. These challenges include (i) the removal of the DC and conjugate image terms, which are features of the holographic recording process, (ii) the reduction of speckle noise, a characteristic of a coherent imaging process, (iii) increasing the angular range of perspective of digital holograms (iv) and replaying captured and/or processed digital holograms using spatial light modulators. Each of these challenges are examined theoretically and several solutions are put forward. Experimental results are presented that demonstrate the validity of the theoretical solutions.